Improving Some Mechanical Properties and Thermal conductivity of PMMA Polymer by using Environmental Waste - Al-Saadi, Tagreed M.; Watan, Anaam W.; Attiya, Hanaa G. (Iraqi Journal of Science, 2021)
This study was achieved to satisfy two goals, the first of which is to treat an environmental problem represented by the disposal of date seeds, and the second is the use of these wastes to improve some mechanical and thermal properties of poly methyl methacrylate PMMA through strengthening different proportions of the powder of date seeds.Particles of date seeds were used as a natural strengthening material for PMMA polymer, by mixing the matrix material (resin) with the hardener while still stirring continuously for a period of 10 min. After that, the samples of the reinforced material were prepared by adding the powder of date seeds, which is the reinforcing substance, with different percentages of weight fraction (0, 0.5, 1, 2, 3, 5 wt. %) and a grain size of <75 µm, while continuing to stir (10 min) for a second time. The composite samples were prepared by the Hand-Lay-up method and cut according to the standard ASTM. Thermal conductivity and some mechanical properties, such as impact strength, tensile strength, compressive strength, flexural strength, and hardness, were studied. An improvement was found in all properties at the reinforcement rate of 1-2 wt. %.